2018
DOI: 10.1021/acsomega.8b02057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Binding of Aripiprazole to Human Serum Albumin: The Importance of a Chloro-Group in the Chemical Structure

Abstract: Aripiprazole (ARP), a quinolinone derivative, is an atypical antipsychotic drug that is used in the treatment of schizophrenia. ARP has an extensive distribution and more than 99% of the ARP and dehydro-ARP, the main active metabolite, is bound to plasma proteins. However, information regarding the protein binding of ARP is limited. In this study, we report on a systematic study of the protein binding of ARP. The interaction of ARP and structurally related compounds with human serum albumin (HSA) was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…PhthaloNH 2 has a rigid structure and is extended in two dimensions, compared to other compounds that have a longitudinally extended appearance and possibly have elements of flexibility, allowing them to bend. Analyzing other reports in the literature, in which albumin has been co-crystallized with longitudinal-looking ligands or having flexible elements, deep binding of phthaloNH 2 to Sudlow’s site I is difficult due to its size and rigidity [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…PhthaloNH 2 has a rigid structure and is extended in two dimensions, compared to other compounds that have a longitudinally extended appearance and possibly have elements of flexibility, allowing them to bend. Analyzing other reports in the literature, in which albumin has been co-crystallized with longitudinal-looking ligands or having flexible elements, deep binding of phthaloNH 2 to Sudlow’s site I is difficult due to its size and rigidity [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…IS was detected using a fluorescence monitor with excitation/emission wavelengths set to 280 and 375 nm, respectively. Plasma ARP concentration was measured by HPLC, as described previously [2]. The HPLC system used in this study consisted of a 655 A-11 pump, 655 A variable wavelength UV monitor (Hitachi Co., Ltd., Tokyo, Japan).…”
Section: Equilibrium Dialysismentioning
confidence: 99%
“…We recently reported that aripiprazole (ARP), 7-(4-(4-(2,3-dichloropheny)-1-piperazinyl) buthoxy)-3,4-dihydro-2-(1H)-quinolinone, a novel antipsychotic agent, binds strongly to two major plasma proteins, namely, human albumin and α1-acid glycoprotein [2,3]. ARP is effective, especially in long-term use.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Ikeda et al made the misleading conclusion that the binding of furosemide to bovine serum albumin is competitively inhibited by indoxyl sulfate, which is one of the typical uremic toxins. 7) To clarify this issue, systematic inhibitory experiments using uremic toxins that bind tightly to HSA should be done.…”
Section: Introductionmentioning
confidence: 99%